Single‐Electron‐Transfer (SET)‐Induced Oxidative Biaryl Coupling by Polyalkoxybenzene‐Derived Diaryliodonium(III) Salts. Issue 44 (17th September 2013) - Yamaoka, Nobutaka; Sumida, Kohei; Itani, Itsuki; Kubo, Hiroko; Ohnishi, Yusuke; Sekiguchi, Sho; Dohi, Toshifumi; Kita, Yasuyuki
Abstract Metal‐free oxidative CC coupling by using polyalkoxybenzene‐derived diaryliodonium(III) salts as both the oxidant and aryl source has been developed. These salts can induce single‐electron‐transfer (SET) oxidation to yield electron‐rich arenes and subsequently transfer the polyalkoxyphenyl group into in situ generated aromatic radical cations to produce biaryl products. The reaction is promoted by a Lewis acid that activates the iodonium salts. It has been revealed that the reactivity of the salts under acidic conditions is quite different to their known behavior under basic conditions. The reactivity preference of a series of iodonium salts in the SET oxidation and their ligand transfer abilities have been systematically investigated and the results are summarized in this report.